SOLID PSEUDOPAPILLARY TUMOR OF PANCREAS WITH ANOMALY OF HEPATIC PORTAL VEIN IN YOUNG FEMALE PATIENT: CASE REPORT - Emilija Nikolovska; Zoran Karadzov; Rozalinda Popova-Jovanovska; Viktorija Calovska; Meri Trajkovska; Darko DJambaz; Mitko Miloshevski; Ljubomir Ognjenovic; Dafina Janevska; Georgi Deriban; Magdalena Genadieva-Dimitrova; Elena Curakova; et al. (Македонско лекарско друштво = Macedonian medical association, 2018)
Solid pseudopapillary tumors are rare tumors of the pancreas, with incidence of about 3% of all pancreatic neoplasms. They are usually found in young females, with nonspecific symptoms (abdominal discomfort, mild abdominal pain, palpable abdominal mass). One third of cases are asymptomatic and diagnosed incidentally. These tumors have a low malignant potential and favorable prognosis after surgical treatment. We present a 17-year-old female patient with abdominal pain during the last three months. Radiological investigations including US, EUS, CT revealed well-defined tumor of the pancreatic head with mixed, solid and cystic pattern. Surgery was recommended, during which an anatomical variation of the hepatic portal vein in the close vicinity of the pancreatic tumor was found. Surgical resection of the tumor was performed; pathohistological specimen defined it as a solid pseudopapillary tumor of pancreas. Diagnosis of solid pancreatic pseudopapillary tumors might be difficult without histopathological evidence, however surgery should be recommended as a treatment of choice and definitive therapy.
СОЛИДЕН ПСЕВДОПАПИЛАРЕН ТУМОР НА ПАНКРЕАС СО АНАТОМСКА ВАРИЈАЦИЈАНА ПОРТНА ВЕНА: ПРИКАЗ НА СЛУЧАЈ
Keywords: pancreatic tumors; solid pseudopapillary tumor; anatomical variations; portal vein; computed tomography; endoscopic ultrasound; ultrasound